Low‐fire processing and microwave dielectric properties of LB glass‐doped Ba3.75Nd9.5Ti17.5(Cr0.5Nb0.5)0.5O54 ceramic. Issue 4 (11th December 2020) - Xiong, Zhe; Tang, Bin; Zhang, Xing; Yang, Chengtao; Fang, Zixuan; Zhang, Shuren
Abstract: The effects of LB glass on the sintering behavior, structure, and dielectric properties for the Ba3.75 Nd9.5 Ti17.5 (Cr0.5 Nb0.5 )0.5 O54 (BNTCN) ceramic were investigated. The results showed that the LB glass, as an effective sintering aid, successfully lowered the sintering temperature of BNTCN ceramic by formation of the liquid phase. Furthermore, the change of the structure and decrease in grain size had influences on the electrical conductivity, thermal stability, and microwave dielectric properties for the BNTCN ceramics doped LB glass. Finally, the excellent microwave dielectric properties with εr  = 73.4, Q × f = 5277 GHz, and τ f  = +7.1 ppm/°C were obtained for samples sintered at 950°C when x  = 5, indicating the BNTCN ceramic doped with 5 wt% LB glass is a promoting LTCC material.